Critical roles of conventional dendritic cells in promoting T cell‐dependent hepatitis through regulating natural killer T cells. (5th January 2017) - Wang, J.; Cao, X.; Zhao, J.; Zhao, H.; Wei, J.; Li, Q.; Qi, X.; Yang, Z.; Wang, L.; Zhang, H.; Bai, L.; Wu, Z.; et al.
Summary: Dendritic cells (DCs) play critical roles in initiating and regulating innate immunity as well as adaptive immune responses. However, the role of conventional dendritic cells (cDCs) in concanavalin A (ConA)‐induced fulminant hepatitis is unknown. In this study, we demonstrated that depletion of cDCs using either CD11c‐diphtheria toxin receptor transgenic mice (DTR Tg) mice or anti‐CD11c antibody reduced the severity of liver injury significantly, indicating a detrimental role of cDCs in ConA‐induced hepatitis. We elucidated further the pathological role of cDCs as being the critical source of interleukin (IL)‐12, which induced the secretion of interferon (IFN)‐γ by natural killer (NK) T cells. Reconstitution of cDCs‐depleted mice with IL‐12 restored ConA‐induced hepatitis significantly. Furthermore, we determined that NK T cells were the target of DC‐derived IL‐12, and NK T cells contributed to liver inflammation and injury through production of IFN‐γ. In summary, our study demonstrated a novel function of cDCs in mediating ConA‐induced hepatitis through regulating IFN‐γ secretion of NK T cells in an IL‐12‐dependent fashion. Targeting cDCs might provide potentially therapeutic applications in treating autoimmune related liver diseases. Abstract : We demonstrated an important role of conventional dendritic cells (cDCs) in the initiation and development of Con A‐induced hepatitis. We define the novel function of cDCs in mediating Con A‐induced hepatitis through regulating IFN‐γ secretion of NKT cells in an IL‐12–dependent fashion.Targeting cDCs may provide a potential therapy in autoimmune related liver diseases.